The Role of Green Innovation as a Competitive Advantage in Manufacturing Companies in the Circular Economy Era - Indria Guntararayana; Rika Septrizarty; Dabitha Wise Maliha; Asrul Mulyadin; Meci Nilam Sari (International Journal of Management and Business Economics, 2026)
This study examines the role of green innovation as a source of competitive advantage for manufacturing firms operating in the context of the circular economy. Using survey data from 280 Indonesian manufacturing firms listed on the Indonesia Stock Exchange (IDX) and registered with the Ministry of Industry, the analysis shows that green innovation, measured through product, process, and organizational dimensions, exerts a significant positive influence on cost leadership, differentiation, and market responsiveness. Structural equation modeling results indicate that green product innovation primarily strengthens differentiation and market responsiveness, while green process innovation has the strongest impact on cost leadership. Green organizational innovation, including environmental management systems and circular supply chain practices, amplifies the effects of product and process innovations on competitive outcomes. The findings further reveal that firm size and industry type act as important moderators, with large firms and resource‑intensive industries benefiting more strongly from green innovation. The study contributes to the resource‑based view and dynamic capabilities literature by demonstrating that green innovation, when integrated with circular economy practices, becomes a strategic resource that enhances both environmental performance and long‑term competitiveness. The results suggest that manufacturing firms in Indonesia should align their green innovation strategies with circular economy principles to achieve sustainable competitive advantage, while policymakers should design targeted incentives and capacity‑building programs to support firms, especially SMEs, in adopting green and circular practices.